Pengaruh Pemberian Sari Kacang Hijau Terhadap Produksi Asi Pada Ibu Nifas: Studi Eksperimen Di Pmb Bidan Sri, Kecamatan Selesai - fani, Tifani Hadi Tri Wahyuni (STIKES Columbia Asia Medan, 2025)
Breast milk (ASI) is the most perfect source of nutrition for infants, especially during the first six months of life. However, many postpartum mothers experience obstacles in producing breast milk optimally. One non-pharmacological alternative to increase breast milk production is the consumption of mung bean extract, which contains lactagogues and B-complex vitamins. This study aims to determine the effect of mung bean extract on breast milk production in postpartum mothers. The method used was a quasi-experimental design with a one-group pretest-posttest approach involving 10 postpartum mothers at PMB Bidan SRI, Selesai Subdistrict, Langkat Regency. The intervention was carried out for seven consecutive days, and data were analyzed using the Wilcoxon Signed-Rank test. The results showed a significant increase in the average breast milk production score from 1.20 to 2.90 after the intervention, with a p-value of 0.004. This indicates that mung bean extract has a positive effect on increasing breast milk production. These findings are expected to serve as a basis for healthcare providers to recommend mung bean consumption in lactation management for postpartum mothers.